Spatial Distribution of Potential Area for Community Forest Development in Grindulu Watershed - Arina Miardini; Pranatasari Dyah Susanti (Geoplanning: Journal of Geomatics and Planning, 2019)
The effect of deforestation on environmental degradation shifted the orientation of forest management into carrying capacity of the watershed. Based on Law No. 41/1999 on Forestry, mandates adequacy forest area defined a minimum of 30% of the watershed area which fulfilled by public forest and private forest. State forest area has limitations, so the development of community forests is needs for optimal forest area in a watershed is required. The purpose of this study was to determine the spatial distribution of potential areas for community forest development in Grindulu Watershed. The potential of community forest was examined through an interpretation of Landsat 8 of 2016 Path/Row 119/668 for land availability and the transformation of NDVI (Normalized Difference Vegetation Index) as the density classifier. The classification of forest density was low density class of 5148.12 hectares or 7.20% (NDVI = 0 to 0.356), moderate density class of 12,076.39 hectares or 16.88% (NDVI = 0.356 to 0.590), and high density class of 54,294.04 ha or 75.92% (NDVI = 0.590 to 0.841). The land available for prioritized community forest development was 37,774.40 hectares (52.82%) in the form of dry-fields, shrubs, grasses, farms, which were located outside the protected areas and production forest. Based on the assessment of field surveys which were conducted proportionally at 89 samples, known good accuracy results by 0.84. Potential area for community forest development was 31,281.54 ha (43.74%) including in Pacitan (9 districts) of 29,111.98 hectares, Ponorogo (5 districts) of 263.29 hectares, and Wonogiri (2 districts) of 1,906.27 hectares.